Book Reviews (Journal of Finance, 1987)
Book reviewed in this article: How Real Is The Federal Deficit? By ROBERT EISNER. New York: The Free Press, 1986. Pp. xvi + 240. Corporate Risk Management: A Financial Exposition . By NEIL A. DOHERTY. New York: McGraw‐Hill, 1985. Pp. xvi + 483. International Financial Markets . By J. ORLIN GRABBE. New York: Elsevier, 1986. Pp. 322 + glossary.